2021
DOI: 10.1007/s10071-021-01536-x
|View full text |Cite
|
Sign up to set email alerts
|

Positional inference in rhesus macaques

Abstract: Understanding how organisms make transitive inferences is critical to understanding their general ability to learn serial relationships. In this context, transitive inference (TI) can be understood as a specific heuristic that applies broadly to many different serial learning tasks, which have been the focus of hundreds of studies involving dozens of species. In the present study, monkeys learned the order of 7-item lists of photographic stimuli by trial and error, and were then tested on "derived" lists. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Thus, if subjects begin the task believing that each stimulus is pre-assigned to a certain rank, it stands to reason that this a priori representation would be resilient against at least some counterfactual information. This view is consistent with previous evidence that when monkeys and humans were shown the "derived" pairings consisting of each stimulus from distinct trained ordered set, they relied on the known ranks held by each stimulus in their original set to judge the novel combination, suggesting that they spontaneously assume that the two sets use the same ranking scale even when there is no logical necessity for this being the case [31,32,33]. More broadly, this view is consistent with the proposed role of generalization heuristics in guiding exploration in complex contexts under high uncertainty [34,35,36].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, if subjects begin the task believing that each stimulus is pre-assigned to a certain rank, it stands to reason that this a priori representation would be resilient against at least some counterfactual information. This view is consistent with previous evidence that when monkeys and humans were shown the "derived" pairings consisting of each stimulus from distinct trained ordered set, they relied on the known ranks held by each stimulus in their original set to judge the novel combination, suggesting that they spontaneously assume that the two sets use the same ranking scale even when there is no logical necessity for this being the case [31,32,33]. More broadly, this view is consistent with the proposed role of generalization heuristics in guiding exploration in complex contexts under high uncertainty [34,35,36].…”
Section: Discussionsupporting
confidence: 89%
“…This view is consistent with other studies in which monkeys and humans were shown “derived” pairings that mixed stimuli from two different pretrained objectively ordered sets. In such tasks, subjects rely on the known ranks held by each stimulus in their original sets to judge the novel across-set combinations, suggesting that they spontaneously assume that the two sets use the same ranking scale even when there is no logical necessity for this being the case ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Popular methods for coding generalization in RL algorithms involve inferring an abstract latent state from one context and applying it to guide learning in a new context ( 39 ). In our case, since each state (each trial) is independent of every other, generalization may be operationalized with the equation , where E ( R | s , a ) is the expected reward given state s and action a and refers to an internal ranking over all stimuli analogous to those proposed in positional inference models in the previous TI literature ( 35 ).…”
Section: Discussionmentioning
confidence: 99%